INOVASI BANTUAN PANGAN NON-TUNAI BAGI MASYARAKAT MISKIN: PROGRAM PENGENTASAN KEMISKINAN DI DESA ABIANSEMAL, KECAMATAN ABIANSEMAL, KABUPATEN BADUNG - Kristina Dewi, Ni Kadek Putri; Kebayantini, Ni Luh; Krisna Aditya, I Gst Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Poverty is one of the problems should be facing by country, no exception for Indonesia. Non-Cash Food Assistance Program (BPNT) is one of the new programs for reduce poverty in Indonesia. This research used qualitative method within description research. There was a theory that used in this research is Defuse Innovation Theory from Everett M Rogers. This research examines the innovation of the Non-Cash Food Assistance program (BPNT) in reduce poverty in Abiansemal Village. Now the innovation in Non-Cash Food Assistance program (BPNT) utilizing technology can bring up some problems. Beneficiary Families (KPM) difficult to receive innovation in implementation to distribute the assistance. Everett M Rogers said that an innovation could not directly adoption by public especially for disadvantaged group category applies to beneficiary families (KPM), because poor society usually belongs to the disadvantaged group category. Keywords: Non-Cash Food Assistance (BPNT), Programs Reduce Poverty, Beneficiary Families (KPM), Innovation